Transgenerational fitness effects of lifespan extension by dietary restriction in Caenorhabditis elegans. Issue 1950 (12th May 2021) - Ivimey-Cook, Edward R.; Sales, Kris; Carlsson, Hanne; Immler, Simone; Chapman, Tracey; Maklakov, Alexei A.
Abstract : Dietary restriction (DR) increases lifespan in a broad variety of organisms and improves health in humans. However, long-term transgenerational consequences of dietary interventions are poorly understood. Here, we investigated the effect of DR by temporary fasting (TF) on mortality risk, age-specific reproduction and fitness across three generations of descendants in Caenorhabditis elegans . We show that while TF robustly reduces mortality risk and improves late-life reproduction of the individuals subject to TF (P0 ), it has a wide range of both positive and negative effects on their descendants (F1 –F3 ). Remarkably, great-grandparental exposure to TF in early life reduces fitness and increases mortality risk of F3 descendants to such an extent that TF no longer promotes a lifespan extension. These findings reveal that transgenerational trade-offs accompany the instant benefits of DR, underscoring the need to consider fitness of future generations in pursuit of healthy ageing.